Instruments Used in Skin Incision (International Journal of Medical and Surgical Sciences, 2015)
The incision is the beginning of every surgical intervention, where separation of the tissues occurs. The uses of thermal mechanisms in skin incisions have been controversial due to higher repair time, necrosis of surrounding tissue, postoperative infection, and poor cosmetic results. The purpose of this study was to determine the evolution of the various types cutting systems and compare the tissue’s response on the use of conventional instrumentation versus diathermy